2018
DOI: 10.2147/opth.s173089
|View full text |Cite
|
Sign up to set email alerts
|

Posterior capsular complication rates with femtosecond laser-assisted cataract surgery: a consecutive comparative cohort and literature review

Abstract: PurposeThe aim of the study was to determine whether femtosecond-assisted laser cataract surgery (FLACS) reduces the posterior capsular complication (PCC) rate compared to manual cataract surgery when performed by an experienced surgeon.Patients and methodsWe reviewed 2,021 consecutive FLACS procedures between 1 June 2012 and 30 August 2017. All cases of posterior capsular rupture (PCR) with or without vitreous prolapse or zonular dialysis (ZD) that prevented an in-the-bag placement of the intraocular lens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…Several studies reporting collectively on nearly 1.3 million cataract surgeries have found rates of posterior capsular tear or vitreous loss ranging from 0.19% to 6.7%. 9,11,20–41 As such, the rate of unplanned vitrectomy reported in this study is similar to or lower than that reported in the literature. Likewise, the incidence of retinal complications for which the patient had to be referred to a retina surgeon (0.072%) was also lower than the literature-reported incidence of retinal detachment/retinal tear (0.18% to 1.4%).…”
Section: Discussionsupporting
confidence: 85%
“…Several studies reporting collectively on nearly 1.3 million cataract surgeries have found rates of posterior capsular tear or vitreous loss ranging from 0.19% to 6.7%. 9,11,20–41 As such, the rate of unplanned vitrectomy reported in this study is similar to or lower than that reported in the literature. Likewise, the incidence of retinal complications for which the patient had to be referred to a retina surgeon (0.072%) was also lower than the literature-reported incidence of retinal detachment/retinal tear (0.18% to 1.4%).…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of posterior capsular rupture varies according to different surgeons. Ocular risk factors include hard nucleus, shallow anterior chamber, previous ocular surgery, or concurrent ocular surgery [ 4 , 39 ]. In our results, only two cases in total (one case in group A and one case in group C) were found with posterior capsular rupture during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…The low PCC rate in FLACS found in these recent RCTs validates the fact that the capsular rupture rate is less than 1% in almost every FLACS series where more than 1000 patients were enrolled. These range from 0.27% (n=1105), 35 0.30% (n=2021), 24 0.31% (n=1300), 2 0.43% (n=1852) 29 and 0.77% (n=3371). 34 Posterior capsular rupture rates were also reported to be less common in eyes operated on by residents (0% vs 3.0%) 36 and (0% vs 3.1%) 37 or in operations on vitrectomized eyes (0% vs 12%).…”
Section: Posterior Capsular Complicationsmentioning
confidence: 99%
“…Improved surgical technique and software upgrades has also reduced the PCR from 7% to 0.3%. 24 The RCT reported by Roberts et al required surgeons to have completed 30 FLACS cases before the trail began. 6 The FACT study required the participants to have undergone 10 supervised FLACS procedures.…”
Section: Learning Curvementioning
confidence: 99%